ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KELENGKAPAN PENGUNGKAPAN INFORMASI LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Manufaktur di BEJ) - JOHAN JOHAN; WIDYAWATI LEKOK (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2006)
The purpose of this research is to analyze the disclosure level in the annual report of the manufacture companies listed in the Jakarta Stock Exchange and also the factors which influence the disclosure level. Those factors are the liquidity, solvability, the firm size, public share, the company's age, profitability, company status, type of the public accountants used by the company, and the leverage level. There are two disclosures level, which are the mandatory and the voluntary disclosures. Data for this research comprises on the information disclosed on the company annual report such as the log total assets, public share percentage, age of the company from first issue date until the research period, the status of the company, the public accountants used by the company and. also the finandal ratios such as current ratio, net profit margin, debt to assets ratio, and debt to equity ratio. The data used in this research are perioded time series cross section data for three consecutive years from 2002 to 2004. This research uses the purposive sampling method. Descriptive stalistics and the multiple regression method were used to analyze the hypotheses. This research finds that the disclosure level in manufacturing companies listed in Jakarta Stock Exchange is quite low whether it is mandatory or voluntary disclosures. The mandatory disclosure is influenced by several variables such as liquidity, the firm size (log total assets), and the type of public accountants used by the company. Then voluntary disclosure is influenced by the solvability and the status of the company.